PEMBERDAYAAN MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS NIAS MELALUI PENGUATAN BUDAYA ORGANISASI DAN KECERDASAN FINANSIAL UNTUK MEWUJUDKAN MAHASISWA UNGGUL - Maria Magdalena Batee; Eliyunus Waruwu; Ainil Warda Lase; Syafirah Nazara; Laurensius Elvantius Gea; Fikri Januarizal Jawa; Stephen Hernandez Hondro; Sentosa Ronal Hulu; Mulya Mulya; Ervin Ningsi Gea (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2026)
Students as candidates for superior human resources need to have academic ability, leadership character, organizational skills, and adequate financial intelligence. However, there are still many students who have limitations in understanding the organizational culture and managing personal finances effectively. This Community Service (PkM) activity aims to improve the knowledge, understanding, and skills of students of the Management Study Program, Faculty of Economics, University of Nias regarding organizational culture and financial intelligence as an effort to realize superior students. The methods used include needs observation, socialization, training, interactive discussions, simulations, financial planning practices, mentoring, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' knowledge which was marked by an increase in the average score from 56.50 in the pre-test to 86.75 in the post-test or an increase of 30.25 points. In addition, there is an increase in students' understanding of organizational discipline, responsibility, communication, teamwork, and leadership. In the aspect of financial intelligence, participants are able to prepare personal financial budgets, record expenses, and understand the importance of savings and financial planning. The preparation and distribution of pocket books as a supporting learning medium also strengthens the sustainability of the program. This activity shows that strengthening organizational culture and financial intelligence through a participatory approach is effective in increasing student capacity and supporting the formation of students who are superior, independent, and ready to face academic and work challenges.